2010
DOI: 10.2136/sssaj2009.0228
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulfur Fertilization and Dynamics in a Brazilian Entisol under Pasture

Abstract: Nutrient dynamics in tropical soils sustaining forage grasses are still poorly understood. We conducted a study to evaluate the effect of combined N and S fertilizer rates on the growth of ‘Marandu’ palisade grass [Brachiaria brizantha (Hochst. ex A. Rich.) Stapf], uptake of these elements from the soil by plants, soil organic matter concentration, soil pH, and the mineral and organic fractions of N and S in an Entisol. Combinations of five N rates (0, 100, 200, 300, and 400 g N m−3) with five S rates (0, 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…2A). Similarly to previous studies of different grasses (Kalmbacher et al, 2005;Salvagiotti et al, 2009;De Bona and Monteiro, 2010), our data show that plant responses to S application enhanced Nuse efficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2A). Similarly to previous studies of different grasses (Kalmbacher et al, 2005;Salvagiotti et al, 2009;De Bona and Monteiro, 2010), our data show that plant responses to S application enhanced Nuse efficiency.…”
Section: Discussionsupporting
confidence: 89%
“…Approximately 55% of the 172 million ha of grassland in Brazil consists of Brachiaria. These grasses are highly productive rhizomatous perennial plants that can respond well to S and N fertilization (De Bona and Monteiro, 2010). The forage responses to S and N fertilization have been extensively reported for other species such as bahiagrass (Paspalum notatum Fluegge): Kalmbacher et al (2005); oat (Avena sativa L.): Wang et al (2002); and ryegrass (Lolium sp.…”
mentioning
confidence: 98%
“…14,15 Sulfur deficiency is a problem that has been reported recently. 16 Numerous studies have shown indirectly that the addition of biochars to soils could increase soil sulfur bioavailability.…”
Section: Introductionmentioning
confidence: 97%
“…The smallest ratio the content of total organic carbon and selected sulphur fraction were the soil type Mollic Fluvisol (Figure 3; depth >0.65 m; C : SS = 16 : 1; C : ClSS = 26 : 1; C : HSS = 17 : 1). Despite the fact that plants absorb S mainly as sulphate, organic S (S directly bonded to C and ester S) pools are important sources of S to plants during their growing season (De Bona and Monteiro, 2010;Freney et al, 1975;Goh and Pamidi, 2003;McGill and Cole, 1981). The process of transformation of organic S to inorganic sulfate (mineralization) and the reverse process (incorporation of sulfate into soil organic compounds or immobilization) play important roles in the cycling of S within the soil and are microbiologically mediated (Kertesz and Mirleau, 2004).…”
Section: Resultsmentioning
confidence: 99%